Is education the best contraception: the case of teenage pregnancy in England? - Girma, Sourafel; Paton, David (Elsevier, 2015)
This paper examines potential explanations for recent declines in teenage pregnancy in England. We estimate panel data models of teenage conception, birth and abortion rates from regions in England. Although point estimates are consistent with the promotion of long acting reversible contraception (LARC) having a negative impact on teenage pregnancy rates, the effects are generally small and statistically insignificant. In contrast, improvements in educational achievement and, to a lesser extent, increases in the non-white proportion of the population are associated with large and statistically significant reductions in teenage pregnancy.